Large Signal Stability Analysis of Three-Phase Bridge Rectifier with Constant Power Loads - อารีรักษ์, กองพล (Srinakharinwirot University Engineering Journal, 2018)
This paper presents the large signal stability analysis of three-phase bridge rectifier with constant power load using linearization technique and phase-plane analysis. The linearization technique is a small signal stability analysis, while the phase-plane analysis is a large signal stability analysis. The analytical results from linearization technique are compared with those from phase-plane analysis. The intensive time-domain simulation using MATLAB is used to verify the analytical results. The results show that the stability analysis using linearization technique cannot provide an accurate result for both small-signal and large-signal conditions. Otherwise, the phase-plane analysis can provide an accurate result with a good oscillation prediction of DC-link filter.